Identify mitigation levels disaster FES Unjaya students based survey knowledge disaster and extension non- structural mitigation management field - Krisna Mutiara Wati; Dian Juliarti Bantam (Jurnal Mantik, 2023)
Objective from this research is know level mitigation disaster FES Unjaya students. Recovery to disaster will need enough time short when public own level mitigation good disaster. This research is based on the problem of para survivor unprepared disaster presence the disaster, even though already know exists threat disaster all around. Such a situation naturally direct impact on time recovery the disaster is getting longer. Student is generation young people who are able to become a driving force or as an agent of change in reduction risk disaster. Hence knowledge disaster and mitigation disaster become very important to realize that thing. Method First that is survey knowledge disaster involving 124 students from management, psychology, law, and accounting study programs and distributed through questionnaires. Based on the survey was obtained as many as 40 students selected for follow counseling mitigation non- structural disasters in the field of management. Method second that is counseling done by design administration of pre-test and post-test. Counseling done verbally or non-verbal. Result of counseling is there is enhancement knowledge moment post test namely 24 students stated own remember mitigation high, 16 students own level mitigation medium, and nothing students who have level low mitigation. This proves exists enhancement knowledge student with it counseling.